Application of fuzzy logic control into power system stabilizer (PSS) for Peninsular Malaysia's national grid system stability enhancement / Joon Ibrahim - Ibrahim, Joon (2009)
This research presents a fuzzy logic power system stabilizer (FPSS) for small signal stability enhancement of The Peninsular Malaysia National Grid System. Simple fuzzy logic control rules are applied. The performance of the FPSS when the system exhibits multi-mode oscillations phenomenon is illustrated. Simulation tests for different operating conditions and disturbances are also discussed. The results are compared with conventional power system stabilizer (CPSS). The comparative results proved the potency of the FPSS. The results demonstrated that the FPSS satisfies two essential properties in the control system field: good damping performance and good robustness. FPSS has enhanced system performances in term of improvement in damping ratio. The system which FPSS had been put into service had exceeded the minimum requirement of 5% damping ratio specified in the Transmission System Reliability Standard. In addition, the system with FPSS had exhibited as much as 18% lower over-shoot. Futhermore, the system with FPSS had an improvement in settling time. Finally, it also has been decisively demonstrated that Fuzzy PSS had enhanced the overall system performance without any needs for re-tuning or changes in setting.